Sociodemographic and Maternal Determinants of Postnatal Care Utilization: A Cross-Sectional Study - Mubarick Nungbaso Asumah Mphil, BscN; Abdulai Abubakari PhD, MSc, BSc; Abdul Malik Abdulai PhD, MPH, BSc; Ruth Nimota Nukpezah PhD, Mphil, BSc, DipN; Fred Adomako-Boateng PhDc, MPH, MD; Abdul-Wadudu Faridu Mphil, BSc; Chrysantus Kubio MD; Bijaya Kumar Padhi PhD, MPH, BSc; Russell Kabir PhD, MPH, BSc (SAGE Publishing, 2023)
Introduction Postnatal care (PNC) is critical for the newborn and the mother, as it offers the opportunity to examine the mother and child to ensure early and timely intervention of any obstetric anomalies that might have gone unnoticed during delivery. However, there is a lack of data on PNC utilization and associated determinants in Ghana. Meanwhile, it is suspected that the PNC service should be more patronized by mothers, particularly within the first 2 days after delivery; therefore, investigating PNC utilization and associated factors could inform policies to enhance PNC uptake. Objective The objective is to determine the level of utilization of PNC service and associated factors in the Savannah region of Ghana. Methods The study used a facility-based analytical cross-sectional study design. The study was carried out in 311 postnatal mothers using consecutive sampling. Data collection was carried out using a questionnaire. Univariate and multiple logistic regression was performed to establish the determinants of PNC. Variables/variable categories with P  < .05 were significantly associated with PNC. The significance level is anchored at P  < .05. Results The study showed that almost all respondents (98.7%) have heard about PNC services through health workers (39.7%), media (13.0%), and friends and relatives (47.2%). Most of the respondents (88.7%) have used PNC services within 48 h. Mothers aged 25-39 years were about seven times more likely to utilize PNC compared to those who were less than 25 years old (AOR [adjusted odds ratio] = 7.41, 95% CI [confidence interval]: 1.98-7.71); mothers with high school education (SHS) and above were also approximately four times more likely to use PNC compared to those who had no formal education (AOR = 3.65, 95% CI 1.97-13.66). In the same vein, married mothers were 10 times more likely to use PNC compared to those who are single mothers (AOR = 10.34, 95% CI: 3.69-28.97), whereas mothers who had at least four antenatal care (ANC) visits during pregnancy were approximately seven times more likely to use PNC compared to those who had less than four ANC visits (AOR = 6.92, 95% CI: 1.46-32.78). Reasons for not attending PNC include waiting time (40.5%), health workers' attitude (32.4%), being attended by a student (16.2%), being busy (27.0%), inadequate information on PNC (24.3%), and no family support (18.9%). Conclusion All mothers knew about the PNC services, with a higher proportion patronizing the services. The increasing age, the level of mothers, marital status, and participation in ANC were significant determinants of the use of PNC. More education during ANC on the importance of PNC service is required to achieve universal coverage of PNC.